Development and Evaluation of a Clinical Decision Support System for Central Venous Catheter Maintenance in the PICU - Wang, Zhenxu (My University, 2021)
Objective To develop a Clinical Decision Support System(CDSS) for Central Venous Catheter (CVC) maintenance in a pediatric intensive care unit (PedN.CDSS-CVC); to evaluate the effect on adherence to Evidence-Based Practice(EBP), the quality of nursing documents and nurses’ perceived effectiveness with PedN.CDSS-CVC; and to explore the impact on Central Line-associated Bloodstream Infection(CLABSI) incidence outcomes. Methods The published literature was systematically searched, and literature types included guidelines, systematic reviews, evidence summaries, and best practice recommendations. Then, we extracted and summarized the evidence on CVC maintenance and established a CVC maintenance pediatric nursing knowledge base (PedN.KB-CVC) containing nursing diagnoses, nursing interventions and nursing outcomes. Clinical nursing experts who were familiar with pediatric intensive care, catheters maintenance and document review were invited to revise the PedN.KB-CVC, rendering the evidence more feasible and appropriate for the clinical workflow and regulations of the hospital. Clinical Care Classification (CCC) was used to code the revised PedN.KB-CVC. A multidisciplinary research team was established to design the PedN.CDSS-CVC function and interface. The design plan was delivered to engineers to perform the system development. The system provided decision-making support throughout the 5 steps of the CVC maintenance nursing process and generated structured document templates to ensure the homogenization and standardization of nursing documents. After the development was completed, a trial run of the PedN.CDSS-CVC was performed from November 1- 30, 2020, in the PICU of Children’s Hospital of Fudan University. During the trial run period, the PedN.CDSS-CVC was gradually improved and optimized according to the feedback from clinical nurses and began to be officially applied on December 1, 2020. A before-and-after study was conducted to examine the effect of CVC maintenance evidence-based practice compliance, the quality of nursing documents, and nurses’ perceived effectiveness with the PedN.CDSS- CVC. All of the above outcome measures from September 1 to October 31, 2020, were addressed as the control group, while those from December 1, 2020, to January 31, 2021, were addressed as the experimental group. We continually included maintenance cases and nursing documents in the two study periods. The Children's CVC Maintenance Evidence-based Practice Assessment Form was created as an instrument and used in on-site observation to explore the changes in EBP compliance; we used the Children's CVC Maintenance and Nursing Document Quality Assessment Form to evaluate the effectiveness regarding the quality of nursing documents and the Clinical Nursing Information System Effectiveness Evaluation Scale to evaluate user nurses’ experience before and after the PedN.CDSS-CVC was implemented. Finally, the incidence of central line-associated bloodstream infection (CLABSI) at the research site before and after the system application was compared over the study period. Results We constructed the PedN.KB-CVC, including 1 nursing diagnosis, 20 nursing interventions, and 3 nursing outcomes. A nursing process CDSS was then designed and optimized, and it could realize functions including automatic identification, automatic content pushing, template generation, automatic links, and warning/reminders. In the evaluation phase, 133 CVC maintenance cases and their nursing documents were included in the control group, while 116 were included in the experimental group. Among the 20 evidence- based practice assessment items, 12 were significantly improved after the system was applied (P<0.05). Regarding nursing document quality, the number of incomplete nursing documents decreased from 24 of 133 to 5 of 116, which was a significant difference (P<0.05). There were 17 of 133 inaccurate nursing documents in the control group and 12 of 116 in the experimental group, and there was no significant difference (P=0.55). Regarding the results of the nurses’ perceived effectiveness with the PedN.KB-CVC, 31 clinical nurses who performed the maintenance practice were included in both the control and experimental groups. The results of the Clinical Nursing Information System Effectiveness Evaluation Scale showed that significant improvement was found in completeness, continuity, reliability, empathy, improved service quality, improved work efficiency, reduced business costs, provided decision support, and improved service processes (P<0.05). However, over the study period, we did not find any significant difference in the CLABSI incidence at the research site (P=0.81). Conclusions The process of constructing a standardized knowledge base for children’s central venous care was scientific and rigorous and was conducive to the homogenization of nursing information. The system ensured a closed loop of the nursing process, improved EBP, improved the quality of nursing documents, and generally improved nurses’ experience with using the system. However, the results of this study cannot prove that the application of this system can reduce the incidence of CLABSI.
Keywords: knowledge base, central venous catheters, clinical decision support system, pediatric, nursing informatics